Changes in Life Goals Over College: A Comparison Between Men and Women Majoring in STEM - Barth, Joan M.; Yang, Yang (Springer Science and Business Media LLC, 2022)
Informed by goal congruity theory and emerging adulthood theory, this study examined changes over time and gender differences in the importance that college STEM majors placed on three life goals that have been hypothesized to explain the differential retention of men and women in STEM: Marriage-Family, Career-Status, and the desire to have a positive Social Impact. 251 students (n = 128, 51% women; n = 191, 76% White) completed three surveys, one year apart. Participants rated the importance of different life goals at each time point. Changes in importance ratings over time were moderated by gender. Men and women only differed in the importance placed on Marriage-Family goals at Time 1 and differences in Social Impact goals emerged at Time 3. Men’s ratings for Marriage-Family and Social Impact goals decreased over time, but women’s ratings did not significantly change. For both genders, ratings of Career-Status goals decreased over time. Secondary analyses suggest that gender differences in Marriage-Family and Social Impact goals emerge midway through college for STEM majors. Findings suggest that women who are retained in STEM majors place a high value on Marriage-Family and Social Impact goals, similar to non-STEM majors, but may be able to better visualize a future STEM career that affords these goals. Explanations for gender differences in STEM interest based on goal congruity theory should consider that the importance of different life goals may change over college.
Keywords: STEM education; Gender differences; Communal goals; Goal congruity theory; Emerging adulthood; Marriage